FEATURES OF THE STATE OF IMMUNE SYSTEM IN PATIENTS WITH CHRONIC MIELOID LEUKEMIA - Выдыборец, Станислав; Майкут-Забродская, Ивана (SWorldJournal, 2022)
Сhronic myeloid leukemia (CML) is a clonal myeloproliferative disease in which as a result of specific translocation of chromosomal sites between 9 and 22 chromosomes, a khimeric BCR-ABL gene with tyrosine kinase activity is formed. The article presents t